Study, conception and analysis of DC-DC buck converter using Matlab/Simulink and Arduino - Hakim, Safa; Bouachrine, Brahim; Bouhouch, Lahoussine; Moudden, Ali (AIP conference proceedings, 2018)
In an energy chain composed of a photovoltaic generator (GPV), a battery module and DC loads, we always opt for treatment the algorithms in order to obtain the maximum power, or the charge and discharge control of the battery, the implementation of algorithms for the management of the system, the regulation of the output voltage. But all, revolves around power converters Buck, Boost, Buck Boost, Cuk, etc. Hence the idea of a primary study of the energy design of this type of converter, especially that the literature does not treat or little this subject. In this work, we realized a Buck converter intended to be used for the control and charging of the battery by a GPV whose command is implemented under Matlab / Simulink through the Arduino Mega 2560 board. The various tests carried out and the results obtained show the good functioning of our system.